Partnering to address rural health workforce challenges in Western NSW. Issue 2 (4th November 2019) - Ramsden, Robyn; Colbran, Richard; Linehan, Tricia; Edwards, Michael; Varinli, Hilal; Ripper, Carolyn; Kerr, Angela; Harvey, Andrew; Naden, Phil; McLachlan, Scott; Rodwell, Stephen
Abstract : Purpose: While one-third of Australians live outside major cities, there are ongoing challenges in providing accessible, sustainable, and appropriate primary health care services in rural and remote communities. The purpose of this paper is to explore a partnership approach to understanding and addressing complex primary health workforce issues in the western region of New South Wales (NSW), Australia. Design/methodology/approach: The authors describe how a collaboration of five organisations worked together to engage a broader group of stakeholders and secure commitment and resources for a regional approach to address workforce challenges in Western NSW. A literature review and formal interviews with stakeholders gathered knowledge, identified issues and informed the overarching approach, including the development of the Western NSW Partnership Model and Primary Health Workforce Planning Framework. A stakeholder forum tested the proposed approach and gained endorsement for a collaborative priority action plan. Findings: The Western NSW Partnership Model successfully engaged regional stakeholders and guided the development of a collaborative approach to building a sustainable primary health workforce for the future. Originality/value: Given the scarcity of literature about effective partnerships approaches to address rural health workforce challenges, this paper contributes to an understanding of how to build sustainable partnerships to positively impact on the rural health workforce. This approach is replicable and potentially valuable elsewhere in NSW, other parts of Australia and internationally.